Análisis de los factores que contribuyen al éxito del Programa “Corazones Excepcionales” de la Asociación Global Health Initiative Perú (GHI) dirigido a personas con síndrome de Down de la provincia de Huánuco una oportunidad de inclusión educativa, periodo 2021-2023 - Vigilio Salas, Meliza Brillyt (2024)
The "Exceptional Hearts" program of the Global Health Initiative Peru (GHI) association supports people with Down syndrome and their families, helping them improve their quality of life and providing opportunities for educational inclusion. The objective of the research was to analyze the determining factors in the success of the "Exceptional Hearts" program, aimed at people with Down syndrome in the province of Huánuco. It was a qualitative case study that employed various sources of information, such as observations, documents, interviews, and focus groups, among other methods. The sample included collaborators from the Global Health Initiative – Peru. Among the main findings, it is highlighted that the program focuses on promoting health, education, and improving the quality of life of families with children with Down syndrome. By basing its approach on the Seven Theses on Health Education for Community Participation, it demonstrates its commitment to educational adaptation founded on dialogue, trust, individual responsibility, and collective cooperation. Additionally, the positive evaluation by families and partners regarding the importance and impact of the program on the development of people with Down syndrome is underscored. The continuous evaluation conducted by Hermilio Valdizán University emphasizes the effectiveness and reciprocity of this initiative, strengthening a solid and mutually beneficial commitment between both parties. Furthermore, it is necessary for the "Exceptional Hearts" program to continue successfully integrating its components and management strategies with the purpose of the GHI Peru (Global Health Initiative) organization, strengthening GHI's hierarchical structure to support the specialized program team. Likewise, it should continue and enhance collaboration with strategic partners. For this purpose, social management facilitates the identification and analysis of processes, which in turn allows for proposing recommendations and improvements in the intervention of programs aimed at people with Down syndrome.